Automatic Monitoring of Soil Conditions For Plants Based On The Internet of Things - Evan, Evan Adicandra; Vianda Putri, Aisyah; Bintang Al Ikhlas, Alif (International Journal of Wireless And Multimedia Communications, 2025)
Abstract—In the current era of digitalization and technological developments, embedded systems have become an important component in various applications, including in the agricultural sector. The Embedded Systems course provides an understanding of the design, development and implementation of efficient and effective integrated systems. One practical application of this knowledge is in the concept of smart farming.Smart farming utilizes embedded system technology to monitor and control various aspects of agriculture automatically and in real-time. By using sensors, microcontrollers and IoT (Internet of Things) devices connected using the ESP32 module